Ornament and Systems of Ordering in the Sixteenth-Century Netherlands. (2019) - Kavaler, Ethan Matt
Abstract : Early modern ornament might profitably be considered as a set of systems, each with its own rules. It signaled wealth and status. It offered pleasure and prompted curiosity. It cut across the apparent divide between the vernacular and the classicizing. It was relational, understood in the context of a given subject but not necessarily subservient to it. The notion of ornament as essentially supplemental and the prejudice against ornamental excess are both children of the late eighteenth century. Both ideas depend on a post-Enlightenment conviction of the work of art as an autonomous, aesthetically self-sufficient object, an idea not fully formed in the early modern era.